COMPRENSIÓN DEL APRENDIZAJE DE LA ARITMÉTICA DESDE LA DIVERSIDAD COGNITIVA: HACIA LA ACCESIBILIDAD - Martínez Cárdenas, Elba Azucena (2026)
The presence of intellectual disability and dyscalculia in regular school classrooms poses a challenge for teachers, particularly due to the low comprehension of mathematics learning from a cognitive diversity perspective. This literature review article highlights the emergence of research in mathematics education aimed at enhancing didactic reflection on understanding the learning processes of students with neurodevelopmental disorders, to promote the design of arithmetic learning environments that are accessible. Cognitive, semiotic, and affective aspects are related to understand cognitive diversity as inherent to every learning environment, and to establish hypothetical learning trajectories, specifically of arithmetic patterns mediated by mathematically structured games. Game-based learning is introduced as a didactic device, related to problem-solving practice, in which heuristics are developed, state changes occur, and affective connections are generated, achieving progression in the learning of arithmetic patterns, in the construction and development of representations from interaction with the other and with others. Finally, the possibility of using electroencephalography in tracking arithmetic learning is considered, in order to demonstrate connections between the aforementioned aspects and the biological response of brain electrical activity during gaming practices.